2001
DOI: 10.1109/77.919881
|View full text |Cite
|
Sign up to set email alerts
|

3-dimensional numerical modelling of rolling of superconducting Ag/BSCCO tape

Abstract: Abstract-Numerical simulation of the deformation process during flat rolling of multifilament HTS tapes has been investigated using a commercial FEM program, ELFEN. The numerical models were built up in 2D and 3D using a DruckerPragerKap model for the powder. Three different roll diameters (024 mm, 0 8 5 mm and 0126 mm) have been investigated.It is found that it is possible to perform numerical simulation with 3D models of flat rolling of multifilament wire. Two 3D models have been used; 3D pressing with rolls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The material properties were extracted from the refs. [10,11], and the BSCCO powder density was obtained as 3.94 g/cm 3 by experimental operation.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The material properties were extracted from the refs. [10,11], and the BSCCO powder density was obtained as 3.94 g/cm 3 by experimental operation.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…3D finite element modelling of flat rolling round wires has been carried out with the FEM program ELFEN investigating the influence of the roll diameter on the flow and density distribution [18]. It has been shown that the diameter has a large influence on the flow.…”
Section: D Fe Analysis Of Flat Rolling Round Multi-filament Wirementioning
confidence: 99%
“…Several efforts had been made in modeling the Bi-2212 powder deformation [26,27], which has mechanical behavior close to soil. The models used to describe the behavior of powders could be divided into micro models based on discrete element considering the particles interaction [28][29][30][31], and macro models regarding powder aggregates as an equivalent continuous material [32,33].…”
Section: Introductionmentioning
confidence: 99%